The Representation of Prophet Muhammad as Rahmatun Lil’ālamīn (A Study of Riffaterre Semiotics in Song Lyrics by Maher Zain) - Adib Alfalah; Asep Sopian; Yayan Nurbayan; Nunung Nursyamsiah (Diwan : Jurnal Bahasa dan Sastra Arab, 2023)
The purpose of this research is to use Michael Riffaterre's semiotic theory to analyse the meaning of the lyrics of the Rahmatun Lil'Alameen song. This is a descriptive-qualitative study. The researchers used techniques such as observing and taking notes. The lyrics to the Rahamatun Lil'Alameen song were obtained from Maher Zain's YouTube channel. The researchers also distributed a Likert scale questionnaire to 30 respondents to determine how well people understood the meaning and impression of Rahmatun Lil'Alameen's song lyrics. The findings of this study are as follows: 1) indirectness of expression includes (a) meaning substitution dominated by metaphorical figurative language, (b) meaning distortion in the form of ambiguity, and (c) the creation of meaning through rhymes, enjambments, and typography that enhance the visual presentation of the verses, 2) Heuristic reading was followed by hermeneutic reading, which described the prophet Muhammad Saw.'s presence as a role model and mercy to all nature, which is imprinted through his compassion and praiseworthy morals. 3) Prophet Muhammad Saw., model: mercy to all creation and blessings on the prophet, as well as variants that run throughout the verses 4) Potential and actual hypograms found in the Qur'an and Hadith that are intertextual. مستخلص يهدف هذا البحث إلى تحليل معنى كلمات الأغنية "رحمة للعالمين" باستخدام نظرية السيميائية لمايكل ريفاتير. من خلال الدراسية الوصفية النوعية. وفي جمع البيانات، استخدم الباحثون تقنيات السماعي والكتابي. ومصدر البيانات الأساسي هو كلمات الأغنية "رحمة للعالمين" التي تم الحصول عليها من قناة ماهر زين على اليوتيوب. وزع الباحثون أيضا استبيانا بمقياس ليكرت على ثلاثين مستجيبا لمعرفة شعور المجتمع في فهم معنى وانطباع كلمات الأغنية "رحمة للعالمين". ونتائج البحث كما يلي: ١) تتضمن اللامبالاة في التعبير (أ) استبدال المعنى الذي تهيمن عليه اللغة التصويرية المجازية، (ب) تشويه المعنى في شكل الغموض، (ج) خلق المعنى بالسجع، والقوافي، و الطباعة التي تجمل الأشعار ،٢) القراءة الإرشادية والقراءة التفسيرية التي تصف شخصية النبي محمد صلى الله عليه وسلم كنموذج يحتذى به ورحمة للعالمين التي تم توصيفها من خلال شفقته وأخلاقه الكريمة، ٣) المصفوفة: النبي محمد صلى الله عليه وسلم، نموذج: رحمة للعالمين والصلاة على النبي صلى الله عليه وسلم، والمتغيرات التي تنتشر في جميع أنحاء المقاطع، ٤) الرسوم التوضيحية المحتملة والفعلية المتوافقة مع القرآن والحديث. الكلمات المفتاحية: السيميائية لريفاتير؛ رحمة للعالمين؛ ماهر زين